2009
DOI: 10.1007/s12016-009-8184-4
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells, Autoantibodies, and Immunologic Infertility: A Complex Interplay

Abstract: Infertility and recurrent spontaneous abortion (RSA) are heterogeneous conditions that have been frequently explained with an immunological pathomechanism. A deeper insight into apparently unexplained infertility and RSA shows increasing evidences supporting both alloimmune and autoimmune mechanisms, in which natural killer (NK) cells and autoantibodies seem to play a relevant role. Successful pregnancy is considered as Th1-Th2 cooperation phenomenon, with a predominantly Th2-type lymphocytes response, togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 92 publications
2
26
0
Order By: Relevance
“…A possible explanation of the IL-18 contribution to successful pregnancy could be through induction of interferon-g expression, resulting in the activation of natural killer cells, which are responsible for uterine vascularization and implantation (39). Evidence supporting this hypothesis are the findings that a large population of natural killer cells is present at uterine and embryonic implantation sites, thus implicating natural killer cells in the process of ''decidualization'' in early stages of pregnancy (39).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation of the IL-18 contribution to successful pregnancy could be through induction of interferon-g expression, resulting in the activation of natural killer cells, which are responsible for uterine vascularization and implantation (39). Evidence supporting this hypothesis are the findings that a large population of natural killer cells is present at uterine and embryonic implantation sites, thus implicating natural killer cells in the process of ''decidualization'' in early stages of pregnancy (39).…”
Section: Discussionmentioning
confidence: 99%
“…83 It has been reported that the modulation in the number of circulating NK cells is most likely to be a primary event rather than an active inflammation or drug-induced consequences during an inflammatory ⁄ autoimmune process, thus playing an important role in the pathogenesis of immunological infertility and pregnancy losses. 20,84 NK cells express inhibitory and activating receptors on their surface. The balance between inhibitory signals from receptors specific for MHC class I molecules [killer inhibitory receptor (KIR)] and stimulatory signals mediated by a variety of activating receptors ultimately determines the outcome of NK cell target encounter.…”
Section: Pro-inflammatory Cytokines Induce Coagulationmentioning
confidence: 99%
“…Another possible explanation could be that CD62L-deficient mice presented with alterations in the IL-15 and IFN-γ cytokine signaling pathways [33] [34] (that affect uNK cell proliferation) resulting in a significantly altered micro environment at the fetal-maternal interface favoring fetal development resulting in larger litters. This could occur via different mechanisms, for example, by preventing homing of NK cells into the decidua, affecting their effector functions (making these cells more regulatory in nature), or by preventing pro-uNK cell trafficking from LNs into the pregnant uterus.…”
Section: Discussionmentioning
confidence: 99%